Using the Health Belief Model to assess COVID-19 perceptions and behaviours among a group of Egyptian adults: a cross-sectional study - Dina N. K. Boulos; Azza Mohammed Hassan (BMC, 2023)
Abstract Background It is crucial to study the public's perceptions and behaviour during a pandemic as this will be the driving force for practicing recommended precautions. The current study aimed to identify perceptions of a group of Egyptian adults to COVID-19 using the Health Belief Model (HBM), to measure self-reported practice of preventive behaviours and to identify influencing factors. Methods Cross sectional study was used, including Egyptian adults aged 18 + years. A structured anonymous online questionnaire was used including: a demographic section, the modified MERS- CoV Health Belief Model scale after addition of questions related to COVID-19 and questions on preventive behaviours to COVID-19. Results Of the 532 study participants, 28.6% were males, age ranges (18 to 74 years). There was a statistically significant positive correlation between total practice score and all COVID-19 Health Belief Model constructs total scores except for perceived barriers score showing negative correlation (P value < 0.05). Linear regression analysis showed that older age, male gender and living inside Cairo were associated with lower practice score (P value < 0.01). Conclusions Increased perceived susceptibility, perceived benefits, cues to action and perceived self-efficacy scores were associated with higher practice score in the current study. Additionally, results revealed that social media and websites can play an important role in shaping risk perception in the community. Stressing risk perception and efficacy beliefs prevention message can drive people to practice preventive behaviors.